2010
DOI: 10.1371/journal.pgen.1000821
|View full text |Cite
|
Sign up to set email alerts
|

Non-Coding Changes Cause Sex-Specific Wing Size Differences between Closely Related Species of Nasonia

Abstract: The genetic basis of morphological differences among species is still poorly understood. We investigated the genetic basis of sex-specific differences in wing size between two closely related species of Nasonia by positional cloning a major male-specific locus, wing-size1 (ws1). Male wing size increases by 45% through cell size and cell number changes when the ws1 allele from N. giraulti is backcrossed into a N. vitripennis genetic background. A positional cloning approach was used to fine-scale map the ws1 lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
73
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(76 citation statements)
references
References 39 publications
2
73
0
1
Order By: Relevance
“…These observations parallel in part earlier findings in Nasonia wasps, in which differential dsx expression in males has been proposed to underlie species-specific differences in male wing size (13). However, dsx expression in male Nasonia differs constitutively between species, whereas in male O. taurus it appears to be altered facultatively in response to nutrition.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…These observations parallel in part earlier findings in Nasonia wasps, in which differential dsx expression in males has been proposed to underlie species-specific differences in male wing size (13). However, dsx expression in male Nasonia differs constitutively between species, whereas in male O. taurus it appears to be altered facultatively in response to nutrition.…”
Section: Resultssupporting
confidence: 86%
“…Third, recent studies have also revealed that dsx is a nexus for the evolution of sexually dimorphic traits; all cases understood at the molecular level involve either changes in cis-regulatory sequences of dsx target genes (11,12) or changes in the expression of dsx itself (13,14). In addition, the recent finding that developing Drosophila are mosaic for dsx expression-and thus are mosaic for the potential for sexual differentiation-has led to increased appreciation for the potential of evolution through tissuespecific changes in dsx activity (15).…”
mentioning
confidence: 99%
“…Evolution at loci with sex-biased expression affects speciesspecific morphology in some insect traits (Barmina and Kopp 2007;Loehlin et al 2010;Wasik et al 2010). The posterior lobe is a male-specific morphological trait, thus the genes important for specifying differences in posterior lobe morphology may show male-biased expression.…”
Section: Sex-biased Gene Expression In the Genital Discmentioning
confidence: 99%
“…The first is the sex determination gene dsx, which directs sex-specific development of the genitalia in Drosophila by regulating the action of patterning genes and Hox genes in the genital imaginal disc (Sánchez and Guerrero 2001;Christiansen et al 2002;Estrada et al 2003). Differences in dsx expression level have been implicated in species-specific wing size differences in male Nasonia wasps (Loehlin et al 2010). The second noteworthy gene is Pox neuro (Poxn), which encodes a transcription factor necessary for proper development of the male genitalia in D. melanogaster.…”
Section: Sex-biased Gene Expression In the Genital Discmentioning
confidence: 99%
See 1 more Smart Citation